Pengaruh Variasi Suhu pada Aerator 10 Watt dengan Panel Surya 80 WP Terhadap Kandungan Oksigen Terlarut - Rachmawati, Putri; Agistya Anugrah, Rinasa; Ulikaryani (Accurate: Journal of Mechanical Engineering and Science, 2022)
The fulfillment of energy for humans and animals is increasing day by day. This is evidenced by the fulfillment of electricity needs. This need is ab basic need, where humans and animals need electricity consumption 24 hours a day. So that renewable energy is needed with solar power generation for 12 hours of electricity. This research is focused on fulfilling electricity consumption in nile tilapia fish with 80 WP slar panels and 10 watt aerator power. The purpose of this study was to determine the level of dissolved oxygen in the water, the temperature in the water and the temperature in the surrounding environment. This research method uses a direct observation of dissolved oxygen with a predetermined data collection time using a dissolved oxygen measuring instrument that can be used in water. The result of this study indicate that the dissolved oxygen content produced is 14.61 mg/l with a thermal in water of 26.30C and thermal environment of around 280C.